"It's a place to feel like part of the community": Counterspace, inclusion, and empowerment in a drop‐in center for homeless and marginalized women. Issue 1 (7th February 2022) - Toolis, Erin; Dutt, Anjali; Wren, Alexander; Jackson‐Gordon, Rachel
Abstract: In the context of rising inequality and eroding safety nets for marginalized communities, research is needed to demonstrate the ways in which settings can facilitate community, agency, and capabilities for low‐income women. The purpose of this study is to examine if and how an organizational setting designed to support homeless, low‐income, and other marginalized women can facilitate empowering changes and increased wellbeing among the women who participate. A thematic analysis of interviews conducted with 22 participants who attend a women's day center identified three ways in which the organizational setting impacted women's lived experiences: (a) increasing a sense of agency through acceptance, active and participatory roles, and ownership over the physical environment, (b) promoting a sense of community through rituals of care and attentiveness, alleviated social isolation, and mutual relationships, and (c) improving life circumstances by offering a safe environment, access to basic resources such as housing, and support for health and wellbeing. Findings highlight the setting features and psychosocial processes that foster flourishing and resist patterns of exclusion and devaluation imposed on marginalized women by dominant neoliberal values, institutions, and policies. Highlights: The study examines how organization facilitates empowering change and wellbeing among marginalized women. Findings document increased sense of agency, sense of community, and improved life circumstances. The setting operates to resist neoliberal values and instead promotes community flourishing.